Mengoptimalkan Kesehatan dengan Digitalisasi: Rekam Medis Elektronik dalam Perspektif Permenkes No 24 Tahun 2022 - Wahyuni, Annisa; Oktavia, Dewi (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Tanah Laut (Politala), 2024)
Based on Minister of Health Regulation No. 24 of 2022, health service facilities must maintain Electronic Medical Records no later than 31 December 2023. RME can improve the quality and safety of health services, reduce adverse incidents for patients, reduce costs, optimize services, improve clinical research, and obtain better clinical outcomes. This community service aims to increase officers' insight regarding digital transformation and RME implementation. The method for community service is giving a pre-test, presenting the material, post-testing, and closing with a question-and-answer session. Activities run smoothly, and the acceptance and knowledge of officers regarding RME have increased. Based on the average level of knowledge of participants during the pre-test with the Know indicator of 70.5%, there was an increase during the post-test, namely 86.5%. The average pre-test score is 65.4% and the post-test score is 84.7%. The knowledge indicator is application with a pre-test average of 62.3% and a post-test average of 82.4%.